PENGARUH PEMBIAYAAN TERHADAP ASET PERBANKAN SYARIAH DENGAN NON PERFORMING FINANCE SEBAGAI VARIABEL MODERATING DI INDONESIA - Surya Tegar Widjiantoro; Lutfi Erwin Lubis (JURNAL AS-SAID, 2021)
This research is using secondary data obtained from the official website of Otoritas Jasa Keuangan (OJK). The data collected was from 2011 - September 2020. This study used MRA (Moderated Regression Analysis) method. This research was conducted to determine whether there is a partial influence and how is the form of moderation Pembiayaan yang disalurkan (PYD) on Islamic banking assets with Non Performing Finance (NPF) as a moderating variable. The results of this study indicate that there is a partial influence of the PYD variable on Islamic banking assets. This is evidenced by the acquisition of t count > t table (42,000>0.7111) and a significant value < α (0,000<0.05). Then the moderating variable in the form of Non Performing Finance (NPF) is able to moderate the relationship between PYD and Islamic Banking Assets. This is evidenced by the acquisition of a significance value in the third regression model (including the interaction variable) which is 0.000, this significance value is smaller than α = 0.05 (0.000<0.05).